The sharp bounds of topological indices of strong product of new f-sum on connected graphs - Siddiqui, Hafiz Muhammad Afzal; Baby, Shakila; Kashifshafiq, Muhammad (Utilitas Mathematica, 2019)
The degree of a vertex v in a graph G is the number of its first neighbors. Degree based topological indices are of much importance because of their vital role in chemical graph theory and particularly in theoretical chemistry. In this paper, the lower and upper bounds for general Randić, general sumconnectivity and harmonic indices for strong product of F-sum on graphs are determined. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.